Experimental study on the influence of Peltier effect on the output performance of thermoelectric generator and deviation of maximum power point. (15th November 2019) - Wang, Jun; Cao, Peiguo; Li, Xingjun; Song, Xiangxiang; Zhao, Chuang; Zhu, Lei
Highlights: An experimental system is set up for studying the Peltier effect. The optimal cooling water flow rate is identified. The impact of Peltier effect on the output performance of TEG is investigated. Peltier effect makes the maximum power point deviate from the theoretical point. Abstract: Thermoelectric generator technology can convert heat into electricity based on Seebeck effect, but the Peltier effect cannot be neglected in the thermoelectric conversion process. In order to explore the influence of Peltier effect on the output performance of thermoelectric generator under the fixed heat transfer boundary conditions, an experimental system is set up. In the experiment, the hot side of the thermoelectric generator is heated by a thermostatic heater which can keep the heating temperature constant, and the cold side is cooled through the convective heat transfer with water. The effect of cooling water flow rate on the open-circuit voltage is first analyzed and the optimum cooling water flow rate is confirmed. Furthermore, the influence of Peltier effect on the cold side temperature and output performance of thermoelectric generator is investigated. The result shows that Peltier effect results in the less actual output power than the theoretical value and makes the maximum power point deviate from the point where the load resistance equals the internal resistance. Besides, as hot side temperature advances from 67 °C to 185 °C, the ratio of load resistance to internal resistance increases from 1.2 to 1.307 in the case of maximum output power.